2015
DOI: 10.7554/elife.08009
|View full text |Cite
|
Sign up to set email alerts
|

LXRs link metabolism to inflammation through Abca1-dependent regulation of membrane composition and TLR signaling

Abstract: The liver X receptors (LXRs) are transcriptional regulators of lipid homeostasis that also have potent anti-inflammatory effects. The molecular basis for their anti-inflammatory effects is incompletely understood, but has been proposed to involve the indirect tethering of LXRs to inflammatory gene promoters. Here we demonstrate that the ability of LXRs to repress inflammatory gene expression in cells and mice derives primarily from their ability to regulate lipid metabolism through transcriptional activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
238
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(248 citation statements)
references
References 39 publications
7
238
1
2
Order By: Relevance
“…Interestingly, LXR activity has been shown to antagonize TLR induced inflammatory gene expression, though whether these signaling pathways are directly tethered has been contentious [23]. However, recent work by Ito and colleagues in macrophages has shown that LXR/ABCA1 induced decreases in raft cholesterol content disrupt TLR4 recruitment of adaptor molecules myeloid differentiation primary response gene 88 (MyD88) and tumor necrosis factor receptor associated factor 6 (TRAF6), preventing downstream inflammatory gene expression [24*] (Figure 1e). …”
Section: Increases In Membrane Cholesterol Impact On Receptor Signalingmentioning
confidence: 99%
“…Interestingly, LXR activity has been shown to antagonize TLR induced inflammatory gene expression, though whether these signaling pathways are directly tethered has been contentious [23]. However, recent work by Ito and colleagues in macrophages has shown that LXR/ABCA1 induced decreases in raft cholesterol content disrupt TLR4 recruitment of adaptor molecules myeloid differentiation primary response gene 88 (MyD88) and tumor necrosis factor receptor associated factor 6 (TRAF6), preventing downstream inflammatory gene expression [24*] (Figure 1e). …”
Section: Increases In Membrane Cholesterol Impact On Receptor Signalingmentioning
confidence: 99%
“…However, in response to low cholesterol levels, sterol regulatory element binding proteins (SREBPs) are activated to increase transcription of the genes involved in fatty acid and cholesterol synthesis [41,42] . Similarly, while the activation of LXRs reduces cholesterol and negatively regulates IL1Btranscription [43] , activation of SREBPs not only increases cholesterol synthesis but also increases inflammasome priming, as shown in human umbilical vein endothelial cells (HUVEC) in vitro, and in mouse aortas in vivo [44] . In this study, ) background, the mice displayed increased atherosclerotic lesion size accompanied by increased expression of inflammasome components in the aortic arch [44] .…”
Section: Inflammasome Priming Via Lipid Metabolismmentioning
confidence: 99%
“…One of the best-characterized mechanisms is the trans-repression of the Toll-like receptor 4 (TLR4) - lipopolysaccharide (LPS) signaling pathway, which is mediated by SUMOylation of the LXR receptor [4]. Recently, upregulation of ABCA1 also revealed anti-inflammation as a critical mediator [37]. To evaluate whether the GW-NPs or Col IV-GW-NPs could repress inflammatory gene expression in macrophages, we pre-incubated peritoneal macrophages for 18 h with 1 μM of free GW, GW-NPs, or Col IV-GW-NPs, followed by stimulation with 100 ng/ml of LPS for 6 h. After the treatments, we isolated total mRNA from the treated macrophages and examined gene expression of the pro-inflammatory marker, monocyte chemoattractant protein-1 (MCP-1).…”
Section: Resultsmentioning
confidence: 99%